(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Research objective: To strengthen the communicative competence of digital content through the WebQuest strategy, using the Wix resource, based on learning by discovery, in the research subject with eleven one graders of the Institución Educativa de Monteria. Qualitative type of research, following the model and route of Pedagogical Action Research that is developed in three phases, namely, deconstruction or self-reflection of the pedagogical action, reconstruction or design of new educational practices and validation of the new pedagogical experience created. Research participants: eleven one graders of the de Monteria school. Research categories: Communication of digital content, digital educational resources and learning by discovery. Survey and observation techniques were used, with the questionnaire instruments, checklist, norm UNE 71361, field diary and rubric, validating their relevance, coherence and sufficiency. The data collected are analyzed using graphs, Google spreadsheet, Padled digital tool and the same UNE 71361. Results of the pedagogical intervention: Participants have habitual handling of social networks to interact spontaneously but lack competence to communicate digital content from standards needed in the knowledge society. It is concluded that discovery learning through the WebQuest strategy is a valid method that strengthens the competence to communicate digital content corresponding to the needs of a world highly mediated by technology and the Internet.